Kinematics and deformation of the southern Red Sea region from GPS observations. Issue 3 (9th March 2020) - Viltres, Renier; Jónsson, Sigurjón; Ruch, Joël; Doubre, Cécile; Reilinger, Robert; Floyd, Michael; Ogubazghi, Ghebrebrhan
SUMMARY: The present-day tectonics of the southern Red Sea region is complicated by the presence of the overlapping Afar and southern Red Sea rifts as well as the uncertain kinematics and extent of the Danakil block in between. Here we combine up to 16 yr of GPS observations and show that the coherent rotation of the Danakil block is well described by a Danakil-Nubia Euler pole at 16.36°N, 39.96°E with a rotation rate of 2.83 deg Myr –1 . The kinematic block modeling also indicates that the Danakil block is significantly smaller than previously suggested, extending only to Hanish-Zukur Islands (∼13.8°N) with the area to the south of the islands being a part of the Arabian Plate. In addition, the GPS velocity field reveals a wide inter-rifting deformation zone across the northern Danakil-Afar rift with ∼5.6 mm yr –1 of east–west opening across Gulf of Zula in Eritrea. Together the results redefine some of the plate boundaries in the region and show how the extension in the southern Red Sea gradually moves over to the Danakil-Afar rift.